Ways And Forms Of Removing Negative Events In The Understanding Of National Identity (Eurasian Journal of Humanities and Social Sciences, 2022)
The article scientifically analyzes the ways and forms of overcoming negative phenomena in the understanding of national identity. On a global scale, political, geopolitical, economic and cultural processes automatically involve each person in one or another system of information flows. As a result, a person has to live and work in an environment of multi-information exchange, which requires significant changes in spiritual characteristics.